PENGEMBANGAN MEDIA PEMBELAJARAN BIG BOOK BERBASIS DIGITAL PADA MATA PELAJARAN PENDIDIKAN PANCASILA SISWA KELAS III SDN 2 LANGSA - Humaira; Asnawi; Ronald Fransyaigu (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
The issue addressed in this study is that the teacher relies solely on picture-based media for delivering Pancasila Education, which leads to a lack of enthusiasm among students. To address this, the researcher developed a digital Big Book focused on the topic “I Obey the Rules” for third-grade students at SDN 2 Langsa. The aim of this research and development effort is to explore the process of developing the Big Book, as well as to assess its feasibility and practicality as a learning tool. This study employed the Research and Development (R&D) method using the ADDIE model, which includes five stages: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. Data were collected through observations, interviews, documentation, and questionnaires. The resulting Big Book media design received highly favorable evaluations: a 90% feasibility score from content experts (classified as “very feasible”), 91% from language experts “very feasible”, and 89% from media experts “very feasible”. Practicality evaluations conducted by teaching practitioners yielded a score of 96.36% “very practical”, while student responses showed a score of 97.12% “very practical”. These results indicate that the digital Big Book developed for the “I Obey the Rules” topic in Pancasila Education is highly appropriate and effective as a learning medium to address the identified issues.